Characterization of Batik Waste Containing Synthetic Textile Dyes and The Artisan Awareness Regarding The Hazardous Batik Waste - Hidayati, Yunin; Siswanto, Dian; Rumhayati, Barlah; Retnaningdyah, Catur (Universitas Negeri Semarang, 2024)
Synthetic textile dyes in the Tanjung Bumi batik coloring process in Madura, Indonesia, have been used extensively for decades, raising environmental concerns due to hazardous wastewater. This research aims to evaluate the quality characteristics of synthetic textile dye wastewater, assess batik artisans' awareness of batik waste hazards, and analyze the interaction between these factors. Wastewater samples were collected from four locations with two repetitions each. Thirty-seven batik artisans participated in a survey. The wastewater analysis included measurements of BOD5, COD, pH, TSS, phenol, Cr, NH3-N, sulfide, and oil and grease. The survey assessed the artisans' use of synthetic dyes and their awareness of environmental hazards. The results showed that the toxic substance levels in Tanjung Bumi batik waste exceed the quality standard thresholds for textile waste. Survey findings indicate that 100% of respondents use synthetic textile dyes, 83.78% dispose of waste without processing, and 91.89% are unaware of the hazards posed by synthetic textile dyes. There is a direct correlation between the artisans' low awareness of the negative impacts of waste and their lack of environmental preservation practices. The novelty of this research lies in its dual evaluation of chemical wastewater characteristics and socio-environmental awareness among artisans. This approach highlights the urgent need for educational interventions and improved waste management practices. The implications are significant for developing sustainable batik production methods and enhancing environmental awareness, contributing to broader societal benefits.